2020
DOI: 10.1001/jamanetworkopen.2020.9072
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Behaviors in Survivors of Smoking-Related and Non–Smoking-Related Cancers

Abstract: IMPORTANCE The population of cancer survivors is rapidly growing in the US. Tobacco smoking is associated with many cancers; however, whether cigarette smoking behaviors among cancer survivors vary according to cancer type-that is, smoking-related cancers (SRCs) vs non-smokingrelated cancers (NSRCs)-remains unclear. OBJECTIVES To examine cigarette smoking prevalence and behaviors (ie, continuing or quitting smoking) among cancer survivors and to compare them between survivors of SRCs and NSRCs. DESIGN, SETTING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 53 publications
2
47
1
Order By: Relevance
“…In a recent analysis of the 2017 NHIS data, 1 in 7 cancer survivors in the United States reported being a current cigarette smoker. 7 Therefore, coordinated action at cancer diagnosis and treatment centers and hospitals, at survivorship clinics, and at the level of primary health care professionals is needed to continue progress toward reducing tobacco-related disease and death among cancer survivors in the United States. Considering that a high proportion of US adult cancer survivors continue to smoke, integration of behavioral and pharmacological cigarette smoking cessation interventions into oncology care is imperative to improve quit rates in this high-risk population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent analysis of the 2017 NHIS data, 1 in 7 cancer survivors in the United States reported being a current cigarette smoker. 7 Therefore, coordinated action at cancer diagnosis and treatment centers and hospitals, at survivorship clinics, and at the level of primary health care professionals is needed to continue progress toward reducing tobacco-related disease and death among cancer survivors in the United States. Considering that a high proportion of US adult cancer survivors continue to smoke, integration of behavioral and pharmacological cigarette smoking cessation interventions into oncology care is imperative to improve quit rates in this high-risk population.…”
Section: Discussionmentioning
confidence: 99%
“… 5 However, the prevalence of cigarette smoking among cancer survivors remains high. 2 , 6 , 7 A recent cross-sectional analysis of the 2017 National Health Interview Survey (NHIS) data reported that 13.2% of US adult cancer survivors were current smokers, 7 but trends in cigarette smoking cessation among cancer survivors have not yet been fully investigated. Because the pattern of cigarette smoking varies substantially according to certain sociodemographic factors, such as sex, race/ethnicity, age, educational level, income, and US Census region, comprehensive temporal trend analysis accounting for these factors and using nationally representative data would be essential for the application of targeted cigarette smoking cessation public health programs.…”
Section: Introductionmentioning
confidence: 99%
“…The following demographic characteristics were included in the analysis: age (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), and 55 years old or older), sex (male or female), race/ethnicity (non-Hispanic white, non-Hispanic black, Hispanic, or non-Hispanic other races), poverty status (<100% of poverty guideline, 100%-199% of poverty guideline, and ⩾200% of poverty guideline), education level (less than high school, high school graduate or equivalent, some college [no degree] or associate degree, bachelor's degree, or advanced degree), residential region (Northeast, Midwest, South, West), and other tobacco product use ("Yes" or "No"). The poverty income guideline was based on the 2015 poverty guidelines for the 48 contiguous states and the District of Columbia.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies reported that after cancer diagnosis, smoking-related cancer survivors have a higher risk of continued cigarette smoking than non-smoking-related cancer survivors. 22 Likewise, another study found that the smoking rate was higher in young cancer survivors (age ⩽40) than in young individuals who had never been diagnosed with cancer. 23 Among samples of cancer patients who smoked cigarettes, about 6.5% to 19% reported current e-cigarette use.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with cancer constitute one group particularly vulnerable to the negative health consequences of smoking [ 4 , 5 , 6 ]. Population-based smoking prevalence estimates among cancer patients vary widely, with some studies reporting a lower smoking prevalence in cancer vs. noncancer patients, [ 7 , 8 ] while other studies have reported a higher smoking prevalence, particularly for those with a smoking-related vs. non-smoking-related cancer [ 9 , 10 ]. The most recent (2017) estimates suggest a generally equivalent prevalence of smoking in cancer vs. noncancer patients (i.e., 13% vs. 14%) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%